2-[1-(2-hydroxy-3-methoxybenzyl)-1H-benzimidazol-2-yl]-6-methoxyphenol monohydrate - Al-Douh, Mohammed Hadi; Osman, Hasnah; Abd Hamid, Shafida; Kia, Reza; Fun, Hoong-Kun (International Union of Crystallography, 2009)
The asymmetric unit of the title compound, C22H20N2O4·H2O, comprises a substituted benzimidazole molecule and a water molecule of crystallization. The dihedral angles between the benzimidazole ring system and the two outer benzene rings are 16.54 (4) and 86.13 (4)°. The dihedral angle between the two hydroxy-substituted benzene rings is 82.20 (5)°. In the crystal structure, intermolecular O-H...O hydrogen bonds, involving the hydroxy groups and water molecules, form R44(8) ring motifs, and link symmetry-related molecules into extended chains along the c axis. The crystal structure is further stabilized by weak intermolecular C-H...O hydrogen bonds, weak C-H...[pi] and [pi]-[pi] stacking [centroid-centroid = 3.6495 (6)-3.7130 (6) Å] interactions. Intramolecular O-H...O and O-H...N interactions are also present.